The Sacred and the Profane in the Organ Music of the Czech Lands in the 19th and 20th Centuries - Jana Michálková Slimáčková (Muzikološki Zbornik, 2015)
The paper focuses on the organ music of Bohemia and Moravia the 19th and 20th centuries. It describes the situation in the area of both church music and organ building. Furthermore, several categories of organ music are dealt with. Finally, several composers are characterized as examples of these categories.